Implementation of Guidance and Counseling Services in Elementary Schools - Hendriani, Maifit; Neviyarni, Neviyarni (International Journal of Educational Dynamics, 2023)
Guidance and counseling services in Elementary Schools (ES) have an important role to play in the holistic development of students. However, the reality in the field is that not all ES have counseling guidance teachers one of them is at ES IT Arafah Padang. The research aims to understand the implementation of guidance and counseling services at ES IT Arafah Padang. Qualitative research with case studies. Data was collected through interviews, observation, and document analysis. The subjects of the study consisted of homeroom teachers of ES IT Arafah Padang, students, and other related parties. Limited funding and resources are the main factors affecting the presence of specialized teachers in guidance and counseling services. Although the service is available, the implementation has not been well programmed regarding the schedule and time of implementation. This causes students to face difficulties in accessing counseling services regularly. In addition, classroom teachers also recognize the lack of effectiveness in identifying students who need services, so some students need help but are not detected. Lack of parental involvement is also a factor influencing service delivery. These findings can be used as a basis for other schools to improve the quality of guidance and counseling services, to support the holistic development of students in ES.